Differential modulatory effects of Propofol and Sevoflurane anesthesia on blood monocyte HLA-DR and CD163 expression during and after cardiac surgery with cardiopulmonary bypass: a preliminary randomized flow cytometry study. (January 2020) - Sbrana, Silverio; Nunziata, Anna; Storti, Simona; Haxhiademi, Dorela; Mazzone, Annamaria; Leone, Maria; Solinas, Marco; Del Sarto, Paolo
Introduction: The increase of the anti-inflammatory CD163 high HLA-DR low blood monocyte subset is one of the mechanisms dampening inflammation during cardiac surgery with cardiopulmonary bypass. We evaluated the effect of two different anesthetic protocols, intravenous Propofol infusion or Sevoflurane-gas administration, on the perioperative frequency of this subset. Methods: Blood from patients (Propofol = 11, Sevoflurane = 13) undergoing minimally invasive mitral valve surgery was drawn preoperatively (T1), before declamping (T2), at 6 (T3), 24 (T4), 48 (T5), and 72 hours (T6) after declamping. C-reactive protein, haptoglobin, and lactate dehydrogenase were measured. A hemolytic index, as C-reactive protein/haptoglobin ratio, was introduced. Monocyte expression of HLA-DR, CD163, and the CD163 high HLA-DR low subset fraction was quantified by flow cytometry. Baseline-referred variations of plasmatic and cellular data at T2 were normalized for clamping times. Subsequent time-point variations were normalized for the final cardiopulmonary bypass times. Results: Variations of hemolytic index and lactate dehydrogenase were higher with Propofol at T3 (p = 0.004 and p = 0.02, respectively) when compared with Sevoflurane. At T2, the down-modulation of CD163 was higher with Propofol (p = 0.005). Starting from T3, the up-regulatory trend of CD163 was basically higher with Propofol, although not significantly. Propofol induced higher increments of HLA-DR low fractions, at T2 (p = 0.04) and, to a lesser extent, at T4 (p = 0.06). Starting from T3, the CD163 high HLA-DR low subset variations were higher with Propofol, especially at T4 and T6. Conclusion: Propofol seems to induce a higher postoperative fraction of the CD163 high HLA-DR low monocyte subset. This could represent either a compensatory mechanism dampening the higher inflammatory condition observed with Propofol at T2 or a consequence of a higher postoperative Propofol-induced hemolysis.